PENGARUH KEBIJAKAN DIVIDEN DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Djuitha, Ribvanny; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this research to determine the influence of dividend policy and profitability on stock price, either simultaneously as well as partially. Dividend Yeild (DY) and Dividend Payout Ratio (DPR) will be used as proxy of dividend policy, and Return on Equity (ROE) and Return on Investment (ROI) will be used as proxy of profitability. Independent variables on this research is DY, DPR, ROE, and ROI, while dependent variable is stock price. Population in research is 48 property and real estate companies listing on Indonesia Stock Exchange period 2012-2016, by purposive sampling is obtained 9 companies as sample. The F-test results showed that variables Dividend Yeild (DY), Dividend Payout Ratio (DPR), Return on Equity (ROE) and Return on Investment (ROI) simultaneously effect on stock price. The t-test result showed that partially Dividend Yeild (DY) and Dividend Payout Ratio (DPR) do not effect on stock price, while Return on Equity (ROE) and Return on Investment (ROI) insignificant effect on stock price. Keyword : dividend policy, profitability, stock price